Herd immunity, vaccination and moral obligation - Bullen, Matthew (Journal of medical ethics, 2023)
The public health benefits of herd immunity are often used as the justification for coercive vaccine policies. Yet, ‘herd immunity’ as a term has multiple referents, which can result in ambiguity, including regarding its role in ethical arguments. The term ‘herd immunity’ can refer to (1) the herd immunity threshold, at which models predict the decline of an epidemic; (2) the percentage of a population with immunity, whether it exceeds a given threshold or not; and/or (3) the indirect benefit afforded by collective immunity to those who are less immune. Moreover, the accumulation of immune individuals in a population can lead to two different outcomes: elimination (for measles, smallpox, etc) or endemic equilibrium (for COVID-19, influenza, etc). We argue that the strength of a moral obligation for individuals to contribute to herd immunity through vaccination, and by extension the acceptability of coercion, will depend on how ‘herd immunity’ is interpreted as well as facts about a given disease or vaccine. Among other things, not all uses of ‘herd immunity’ are equally valid for all pathogens. The optimal conditions for herd immunity threshold effects, as illustrated by measles, notably do not apply to the many pathogens for which reinfections are ubiquitous (due to waning immunity and/or antigenic variation). For such pathogens, including SARS-CoV-2, mass vaccination can only be expected to delay rather than prevent new infections, in which case the obligation to contribute to herd immunity is much weaker, and coercive policies less justifiable.